Analisis Survei Pressure, Temperature, Spinner (PTS) pada Sumur Dominasi Air di Pulau Sumatera, Indonesia untuk Menentukan Kualitas Feedzone - Afif Habiburrahman, M
Pressure, temperature, spinner (PTS) is one of common testing which is done at geothermal wells. As the name, this testing provides pressure, temperature, and spinner rotation velocity distribution along the well. The purpose of this testing is to estimate feedzone depth and its quality. Feedzone depth can be estimated by the change of mass rate along the well which then can be confirmed by pressure difference and temperature change at the point. Then, feedzone quality can be estimated from the Productivity Index or Injectivity Index value. Productivity Index is a parameter that illustrates the effect of pressure changes to the rate of production, while the Injectivity Index illustrates the effect of pressure changes to the rate of injection. Analysis of this study based on the PTS Injection and PTS Flowing survey. The difference is at the PTS injection survey, some fluid is injected to the well with a constant rate, while the well is producing when the PTS flowing survey. This paper explained the steps of analysis of PTS Survey data to estimate feedzone quality, also the simulation that has done for the PTS flowing survey. The simulation is done to match the interpretation with the real data, in which there are fractional fluid changes inside the well. As an example, the PTS survey in water dominated well at Sumatera, Indonesia used. Three feedzones are found for each testing, both flowing and injection.